2022
DOI: 10.1038/s41586-022-04785-z
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal dynamics and natural history of clonal haematopoiesis

Abstract: Clonal expansions driven by somatic mutations become pervasive across human tissues with age, including in the haematopoietic system, where the phenomenon is termed clonal haematopoiesis1–4. The understanding of how and when clonal haematopoiesis develops, the factors that govern its behaviour, how it interacts with ageing and how these variables relate to malignant progression remains limited5,6. Here we track 697 clonal haematopoiesis clones from 385 individuals 55 years of age or older over a median of 13 y… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
223
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 189 publications
(277 citation statements)
references
References 61 publications
29
223
0
Order By: Relevance
“…The VAF of the majority of DNMT3A mutations did not change between the two time points analyzed (Figures 2E-F). This is consistent with a recent report demonstrating rapid expansion of DNMT3A -mutant clones early, but rather slow growth later in life 51 . Nevertheless, within the frequent donor cohort, 4 out of 16 DNMT3A mutations analyzed displayed a 1.5-3-fold increase in their VAF (Figure 2E and Supplemental Table 6).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The VAF of the majority of DNMT3A mutations did not change between the two time points analyzed (Figures 2E-F). This is consistent with a recent report demonstrating rapid expansion of DNMT3A -mutant clones early, but rather slow growth later in life 51 . Nevertheless, within the frequent donor cohort, 4 out of 16 DNMT3A mutations analyzed displayed a 1.5-3-fold increase in their VAF (Figure 2E and Supplemental Table 6).…”
Section: Resultssupporting
confidence: 93%
“…Accordingly, our analysis of consecutive samples confirmed that the VAF of the majority of DNMT3A mutations remains stable. This is consistent with a recent long-term follow-up study showing that DNMT3A mutations are more likely to expand early in life and display a slower growth in older age 51 . The current paradigm in the field is that specific cues from the environment are necessary to favor the outgrowth of HSPCs carrying mutations they acquire during the course of life 24,25,51,63 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Third, the fitness effect of a mutation could itself be dependent on genotype and age. A recent study has reported DNMT3A mutant clones whose fitness advantage decreases with age ( 7 ). If such an effect existed for mCAs it would be expected to produce weaker age dependence.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in haematopoietic stem and progenitor cells (HSPCs) which confer a 'Darwinian' fitness advantage can clonally expand to detectable levels in blood -a phenomenon known as clonal haematopoiesis (CH) (1)(2)(3)(4). Previous studies have developed population genetic frameworks for estimating the mutation rates and associated fitness effects of these mutations (5,6) and these estimates have been validated in subsequent studies leveraging serial sampling (7) and single-cell derived phylogenies (8). These previous analyses have largely focused on the fitness effects and mutation rates of single nucleotide variants (SNVs) in cancer-associated genes.…”
Section: Introductionmentioning
confidence: 99%